2022
DOI: 10.1039/d2ra01673g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning polymorphs of precipitated calcium carbonate from discarded eggshells: effects of polyelectrolyte and salt concentration

Abstract: Tuned spherical vaterite calcium carbonate polymorphs have been precipitated from discarded eggshells and loaded with silver nanoparticles by in situ synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Furthermore, the bands at 1089 and 840 cm –1 are attributed to C–O and C–C stretching vibrations, respectively. The spectra of CaCO 3 –Ag-CMC and CaCO 3 –Ag-PSS show four vibrational modes of carbonate ions at 1395 cm –1 assigned to asymmetric stretching, at 1014 cm –1 attributed to symmetric stretching, at 872 cm –1 assigned to out-of-plane bending, and at 713 cm –1 ascribed to in-plane bending vibrations and one vibrational mode of AgNPs at 552–582 cm –1 . CaCO 3 –Ag-PSS and CaCO 3 –Ag-CMC microspheres (7.5 wt %) in the PVA polymer matrix lead to the shift of some peaks and change of relative intensities.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the bands at 1089 and 840 cm –1 are attributed to C–O and C–C stretching vibrations, respectively. The spectra of CaCO 3 –Ag-CMC and CaCO 3 –Ag-PSS show four vibrational modes of carbonate ions at 1395 cm –1 assigned to asymmetric stretching, at 1014 cm –1 attributed to symmetric stretching, at 872 cm –1 assigned to out-of-plane bending, and at 713 cm –1 ascribed to in-plane bending vibrations and one vibrational mode of AgNPs at 552–582 cm –1 . CaCO 3 –Ag-PSS and CaCO 3 –Ag-CMC microspheres (7.5 wt %) in the PVA polymer matrix lead to the shift of some peaks and change of relative intensities.…”
Section: Resultsmentioning
confidence: 88%
“…The stable silver colloid was prepared by adding 0.01 M silver nitrate solution to the polyelectrolyte solution under stirring at ambient temperature. The calcium nitrate solution was obtained from eggshell powders, as described in our recent publication . The calcium nitrate molar concentration was adjusted, and the pH was altered to about neutral by adding 0.1 molar sodium hydroxide solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, sustained release of the drug was obtained from the tablet formulations containing modified eggshell particles. Recently, silver nanoparticles loaded with calcium carbonate (Ag/CaCO 3 ) particles were prepared by precipitation technique and reported by Azarian et al (Azarian and Sutapun, 2022). As illustrated in Figure 11, spherical precipitated calcium carbonate (PCC) particles were deposited by silver nanoparticles and energy-dispersive X-ray spectroscopy mapping (EDS) images depicted a clear spherical pattern, indicating their loading at the outer layer of PCC particles with sliver atomic weight percentage of 4.27 wt%.…”
Section: Nanoparticle's Carrier and Drug Deliverymentioning
confidence: 96%
“…However, the eggshells or seashells waste can be digested in acid and reformed in highly controlled conditions in the precipitation technique. Azarian et al (Azarian and Sutapun, 2022) have recently precipitated the calcium carbonate particles from eggshells and showed that morphologies and polymorphs structures of precipitated calcium carbonate (PCC) particles could be effectively tunned by changing the experimental parameters such as initial calcium ions molar concentration, using different polyelectrolytes (non-ionic or ionic) with different molecular weight, and concentration of polyelectrolyte solution. The advantages of this technique are the possibility of controlling the size and obtaining calcium carbonate with desired morphologies, i.e., star-shaped, yarn or spherical shapes with various polymorph crystal structures such as vaterite or calcite.…”
Section: Composition/elementsmentioning
confidence: 99%